Pengaruh Motivasi Belajar dengan Prestasi Belajar Ekonomi Siswa di SMK Mahadika Ciracas - Syarifah Nurul Mulki (Neolectura, 2019)
This research aimed to know how big effect of learning motivation on student achievement studying economics at Mahadika Ciracas vocational high school. The research used a quantitative method with descriptive approach. Population in this research is all of accounting students X grade 1 and 2 at SMK Mahadhika Ciracas with a total of 67 students. Because the sample is less than 100, the entire population is also used as a research sample. To test data analysis using method of Product Moment Correlation, Coefficient of Determination and Hypothesis test. Conlucions is there are no effect between the influence of learning motivation on student achievement studying economics at mahadika ciracas vocational high school. It can be the results of t_ count = 0.533 with t_ table = 1,670 at the level of 5% = and dk = N-2 = 67-2 = 65, so the value of t-count ? table. Which means that Ha was rejected and Ho was accepted.